2022
DOI: 10.1177/00219096211069650
|View full text |Cite
|
Sign up to set email alerts
|

Organized Crime–Terror Nexus: Interrogating the Linkage Between Banditry and Terrorism in Northern Nigeria

Abstract: This paper examines the phenomenon of crime–terror nexus from the standpoint of the linkage between banditry and Boko Haram insurgency in Northern Nigeria. Using a descriptive analysis predicated on a combination of primary and secondary studies, the paper reveals that both groups have functionally adapted each other’s structures and strategies. While Boko Haram and its splinter groups have occasionally engaged in acts of banditry, there has been mutual co-option by both groups as the exigencies of their opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The second plausible explanation is to be found in the increasingly integrated nature of crime in the country. For instance, just as it has been amply demonstrated that there is a strong nexus between banditry in the north east and terrorism in the northwest [ 52 ], there is a sense in which it could be argued that rampant kidnapping for ransom in the southern zones of the country fed into both banditry and terrorism by helping to raise money for the activities of both groups. This position is supported by the fact that most of the kidnap victims in the southern part of the country testified that their abductors were unmistakably of northern or Arab origin judging by their looks, language and/or accent.…”
Section: Discussionmentioning
confidence: 99%
“…The second plausible explanation is to be found in the increasingly integrated nature of crime in the country. For instance, just as it has been amply demonstrated that there is a strong nexus between banditry in the north east and terrorism in the northwest [ 52 ], there is a sense in which it could be argued that rampant kidnapping for ransom in the southern zones of the country fed into both banditry and terrorism by helping to raise money for the activities of both groups. This position is supported by the fact that most of the kidnap victims in the southern part of the country testified that their abductors were unmistakably of northern or Arab origin judging by their looks, language and/or accent.…”
Section: Discussionmentioning
confidence: 99%
“…Criminal groups engage in these activities to generate revenue, leading to significant social and economic consequences (Agnew, 2020). The use of violence and coercion is a common tactic used by criminal groups engaged in banditry (Okoli & Nwangwu, 2022). Counter-banditry measures, such as law enforcement and judicial reform, can have mixed results (Obi & Iwuoha, 2023).…”
Section: Banditrymentioning
confidence: 99%
“…Counterinsurgency operations have remained a mirage in North-East Nigeria despite claims of defeating Boko Haram by the Nigerian government. Available pieces of evidence prove that Nigeria’s commitment to ending the menace of Boko Haram has not produced the expected result as the insurgency has either intensified or mutated into what is widely deodorized as “banditry” within the past 7 years (Okoli & Nwangwu, 2022). As established earlier, the challenges bedeviling Nigeria’s counterinsurgency strategies are associated with state fragility.…”
Section: Dissecting the Challenges To The Military-led Counterinsurge...mentioning
confidence: 99%